2021
DOI: 10.3390/plants10102051
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence of Model Crop Brassica napus L. in Soil Clean-Up: Comparison of Tolerance and Accumulation of Lead and Cadmium

Abstract: The potential of the model crop Brassica napus L. (rapeseed) for the phytoremediation of soils polluted with metals was investigated at laboratory scale. The first step consists in the evaluation of the seed germination and growth of the Brassica napus L. plant in a controlled environment, followed by the determination of the photosynthetic pigments content represented by chlorophyll a and b and carotenoids. The degree of metal accumulation in rapeseed has been evaluated by the bioaccumulation factor (BAC), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Previously, Gul, Manzoor [ 58 ] studied Pb-ions' translocation from roots to the vegetative regions and stated that Pb may require transportation through the xylem [ 58 ]. Further, the accumulation of high concentration of Pb was observed near the phloem and xylem cells in many plants through the X-ray mapping technique, which further confirmed that phloem vessels are also involved in Pb transport along with xylem vessels [ 59 ].…”
Section: Uptake Accumulation and Transportation Of Pb-metal In Plantsmentioning
confidence: 78%
“…Previously, Gul, Manzoor [ 58 ] studied Pb-ions' translocation from roots to the vegetative regions and stated that Pb may require transportation through the xylem [ 58 ]. Further, the accumulation of high concentration of Pb was observed near the phloem and xylem cells in many plants through the X-ray mapping technique, which further confirmed that phloem vessels are also involved in Pb transport along with xylem vessels [ 59 ].…”
Section: Uptake Accumulation and Transportation Of Pb-metal In Plantsmentioning
confidence: 78%
“…However, due to the continuous increase of environmental pollution caused by the demands of consumerism, researchers have come up with high concerns on safety and quality issues related to the use of herbal products [1,2]. Inorganic pollutants, such as heavy metals, represent a wide interest category of pollutants for risk studies due to their impacts on the environment and on human health [3,4]. According to the World Health Organization (WHO), heavy metals are some of the most dangerous pollutants; non-degradable, they bioaccumulate in the environment, transfer through the food chain, and induce negative effects on the environment and human health [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the study of the cadmium content of certain plant foods and waters, it is essential to investigate the Cd removal from soil and water. Many physical and chemical methods have been used to remove heavy metals from soils and wastewaters [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%